Regulation of redox status in neuronal SH-SY5Y cells by blueberry (Vaccinium myrtillus L.) juice, cranberry (Vaccinium macrocarpon A.) juice and cyanidin. (August 2018) - Cásedas, Guillermo; González-Burgos, Elena; Smith, Carine; López, Víctor; Gómez-Serranillos, María Pilar
Abstract: Blueberry and cranberry are fruits with high polyphenol content, particularly anthocyanins. As cyanidin derivatives have been identified as one of the most representative polyphenols in berry juices, cyanidin has been designated for a better comparison and understanding of the potential neuroprotection of juices obtained from two Vaccinium species. Neuroblastoma SH-SY5Y cells were previously treated with different concentrations of lyophilized blueberry juice, cranberry juice or cyanidin for 24 h and oxidative stress was then generated with hydrogen peroxide (100 μM) for 30 min. Cytoprotective properties of cranberry juice, blueberry juice or cyanidin were evaluated using different methodologies such as mitochondrial activity (MTT), TBARS and ROS production, antioxidant enzymes (CAT, SOD) and antioxidant properties (ORAC, FRAP). Results indicated that blueberry and cranberry juices as well as cyanidin increased mitochondrial activity and reduced intracellular ROS production and lipid peroxidation induced by hydrogen peroxide. Furthermore, these berry juices and cyanidin upregulated the activity of the antioxidant enzymes catalase and superoxide dismutase. Finally, in vitro antioxidant capacities were confirmed by ORAC and FRAP assays demonstrating the potential of cyanidin and cyanidin-containing products for pharmaceutical or nutritional applications to prevent oxidative stress in neuronal cells. Graphical abstract: Highlights: Cyanidin, cranberry juice and blueberry juice decreased ROS and TBARS levels in neuronal cells. Catalase and superoxide dismutase activities were upregulated by cranberry juice, blueberry juice and cyanidin. Cyanidin acts as a neuroprotective agent against hydrogen peroxide induced cytotoxicity.